Website-Based Digitalization of Fisheries MSMEs in Puntondo Village, Takalar Regency - Hasnawiya Hasan; Muhammad Alief Fahdal; Haliah .; Imran Oemar; Idayanti .; Surya Haryanto; Muhammad Afrial Ivan Pratama (Faculty of Engineering UNHAS, 2025)
The fishing community in Puntondo Village, Takalar, relies heavily on income generated from the INS MSMEs. However, their business activities remain relatively simple and have yet to leverage digital markets [1], which limits their distribution reach, operational efficiency, and marketing effectiveness. The aim of this community service program is to transform the fisheries sub-sector—specifically the INS Fisheries MSMEs in Takalar—from a conventional system into a website-based digital system. Digitalization is utilized to address issues such as lack of clarity, limited market coverage, operational inefficiency, competitiveness, and customer trust. As a result, the digitalization of the fisheries sector through website integration is expected to significantly enhance operational efficiency, revenue generation, and consumer confidence. Information technology and digitalization are crucial for the continued development of fisheries-based MSMEs, which in turn can improve the coastal economy [2]. This transformation has a profound impact on digital branding, marketing strategies, and information transparency. Accordingly, management training, technology mentoring, inventory system integration, and online marketing have been carried out. Several case studies have shown improvements in market reach, transaction speed, and the professional image of INS MSMEs. The website aids in product distribution and SEO optimization, thereby enhancing credibility. Additionally, the INS MSME is the central subject in outreach efforts involving local fishermen and communities. The observation method includes analysis of sales activities before and after the website launch, as well as monitoring of website usage and consumer engagement online. The analytical method comprises a qualitative analysis of the digitalization program’s impact on micro, small, and medium enterprises (MSMEs), including changes in market reach, operational efficiency, and customer perception, along with empirical comparisons through case study analysis. The primary output of this program is a dedicated MSME website for promotion and transactions, designed around a digital inventory management system, SEO-based marketing, and strengthened customer engagement through social media. This aligns with community development theories, particularly the empowerment of coastal communities through technological and interdisciplinary (technical and economic) approaches to MSME growth. In the results and discussion section, it is described that the main outcome is a functional, SEO-friendly website, which has significantly expanded its national market reach and improved transactional efficiency by reducing manual errors. The specific impacts of the program include enhanced operational efficiency, online ordering, real-time inventory tracking, increased product visibility on Google and e-commerce platforms, improved credibility through customer testimonials, and higher MSME revenue. More significantly, the program has opened opportunities for partnerships with investors and business collaborators, allowing MSMEs to compete digitally with larger platforms. In conclusion, collaboration through digitalization has proven to enhance MSME competitiveness and create partnership and investment opportunities. Nevertheless, challenges such as limited infrastructure and data security threats remain. Therefore, website-based digitalization of fisheries MSMEs is highly effective in advancing the local economy, expanding market reach, and ensuring the sustainability of operational efficiency.